Simple Floating Ocean Wave Energy Converter: Developing Teaching Media to Communicating Alternative Energy - Satriawan, Muhammad; Rosmiati, Rosmiati (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
Research aims to develop teaching media in communicating alternative energy to students who are in high school. The teaching media developed as a prototype converter of ocean wave energy into electrical energy. This Converter is focused on helping students understand concepts and technologies in utilizing ocean wave energy as an alternative energy source. The development stage adopted the ADDIE model, which is limited to the analysis, design, and development stages. The data obtained are in the form of design validation data, trial data, and product assessment data. The data were analyzed using descriptive statistics. Based on the results of data analysis, it is found that (1) the converter design is feasible to be developed with a few additions to the transmission section to produce higher RPM; (2) the resulting converter functions correctly with the output voltage of 5 to 9 volts in the artificial wave pool test and reaches 8 to 12 volts; (3) for product assessment, it was found that the Converter produced was suitable to be used as a teaching medium to communicate concepts and technology in utilizing ocean wave energy as an alternative energy source. So, teaching media in the form of a wave energy converter could be used as an alternative to communicating the concept of using ocean waves as an alternative energy source. The implication of this research is that it can be used as a model or initial example in developing learning media related to alternative energy and can even be used as a model in developing converters on a larger scale so that the wider community can use them.